Lessons from the past - Abd Razak, Dzulkifli (2010)
WORLD Environment Day, which is celebrated every June 5, took the theme Biodiversity Ecosystems Management and the Green Economy this year. The day has been dubbed "the main weapon of the United Nations" to make people aware of worldwide environmental destruction and draw the attention and action of various political sources. This year there is no lack of attention grabbers although we cannot say the same for the effectiveness of the efforts taken so far.